Peran Pendidikan Agama Hindu Dalam Pengembangan Sumber Daya Manusia Yang Berkualitas - IG Agung Jaya Suryawan (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2021)
Religion is the inner power or inner power for its adherents in various life challenges. Religion has clearly given the character of life for humans, which is actually the most fundamental problem for humans. The essence of the purpose of life in Hinduism is formulated with sentences. Moksartham jagathitayaca iti Dharma. The goal of life is to attain the jagathita and moksa. This is then described in the teachings of Chess Purusa Artha, namely: Dharma, Artha, Kama, Moksa. The purpose of life is then to animate a social order called Dormitory Chess (brahmacari, grhasta, vanaprastha, and sannyasa) and Catur Warna, namely: Brahmana, Ksatriya, Vaisya, Sudra). Thus Hinduism clearly and firmly establishes the essence of the purpose of life as well as the way to achieve it, including the social order as a means to achieve it in order to realize human beings with divine, good and noble characters. So Hinduism can not only provide insight and a clear vision for people in facing life, but will also build integrity for its adherents. Keywords: Education Shapes Character